1983
DOI: 10.3758/bf03196976
|View full text |Cite
|
Sign up to set email alerts
|

On the conflict between logic and belief in syllogistic reasoning

Abstract: Three experiments are reported that investigate the weighting attached to logic and belief in syllogistic reasoning. Substantial belief biases were observed despite controls for possible conversions of the premises. Equally substantial effects of logic were observed despite controls for two possible response biases. A consistent interaction between belief and logic was also recorded; belief bias was more marked on invalid than on valid syllogisms. In all experiments, verbal protocols were recorded and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
540
4
13

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 694 publications
(629 citation statements)
references
References 34 publications
43
540
4
13
Order By: Relevance
“…The interaction effect described by Evans et al (1983) can thus be estimated by a contrast of contrasts. This measure, often referred to as the interaction index, has provided the basic datum for a substantial number of studies that have investigated the Belief ϫ Logic interaction (e.g., Ball, Phillips, Wade, & Quayle, 2006;Evans et al, 1983;Evans & Curtis-Holmes, 2005;Evans, Newstead, Allen, & Pollard, 1994;Morley, Evans, & Handley, 2004;Newstead, Pollard, Evans, & Allen, 1992;Quayle & Ball, 2000;Roberts & Sykes, 2003;Shynkaruk & Thompson, 2006;Stupple & Ball, 2008;Thompson, Striemer, Reikoff, Gunter, & Campbell, 2003). Rewriting the index, we can denote P("Valid"|Valid) as H (the hit rate), and P("Valid"|Invalid) as F (the false-alarm rate).…”
Section: ______________________________mentioning
confidence: 99%
See 3 more Smart Citations
“…The interaction effect described by Evans et al (1983) can thus be estimated by a contrast of contrasts. This measure, often referred to as the interaction index, has provided the basic datum for a substantial number of studies that have investigated the Belief ϫ Logic interaction (e.g., Ball, Phillips, Wade, & Quayle, 2006;Evans et al, 1983;Evans & Curtis-Holmes, 2005;Evans, Newstead, Allen, & Pollard, 1994;Morley, Evans, & Handley, 2004;Newstead, Pollard, Evans, & Allen, 1992;Quayle & Ball, 2000;Roberts & Sykes, 2003;Shynkaruk & Thompson, 2006;Stupple & Ball, 2008;Thompson, Striemer, Reikoff, Gunter, & Campbell, 2003). Rewriting the index, we can denote P("Valid"|Valid) as H (the hit rate), and P("Valid"|Invalid) as F (the false-alarm rate).…”
Section: ______________________________mentioning
confidence: 99%
“…Evans, Barston, and Pollard (1983), in an important early study of belief bias, showed that the believability of a given syllogistic conclusion can have drastic effects on the probability that subjects will endorse it. In three experiments, subjects were asked to evaluate the validity of four types of syllogisms, which resulted from crossing the logical status and believability of the conclusions.…”
Section: ______________________________mentioning
confidence: 99%
See 2 more Smart Citations
“…One problem is that people, especially children (Ward & Overton, 1990), have a tendency to confuse truth with validity and reason based upon what they want to believe rather than using rules of logic (e.g., Evans, Barston, & Pollard, 1983;Henle & Michael, 1956;Wilkins, 1928). A second problem is that the context of the syllogism topic influences how people judge its validity (e.g., Braine, 1978;Evans, 1989;Ward & Overton, 1990); for example, a syllogism of the same form may be judged differently depending on whether the topic is safety belts or high school parties.…”
Section: Figure 4: Percent Of Children Mastering Class-inclusion Syllmentioning
confidence: 99%